Integrating Nature-Based Solutions for Increased Resilience to Urban Flooding in the Climate Change Context - George Radu; Maria Ilinca Chevereșan; Sorin Perju; Alina Bărbulescu (Hydrology)
As climate change intensifies with more frequent and severe flood events, urban areas face increasing challenges to protect population wellbeing. Amid urban development challenges, political uncertainty, and socioeconomic pressures, finding sustainable solutions to enhance urban resilience has become urgent and complex. This article explores the limitations of traditional drainage systems in an urban zone of Bucharest, Romania, and the integration of nature-based solutions for flood mitigation. We compare the existing situation with those simulated in a climate change scenario before and after implementing green solutions. The imperviousness of parking lots was set at 60%, that of green roofs at 65%, and that of parking lots at 85%. A hydraulic model was used for this purpose. The results demonstrate that the current stormwater systems struggle to meet the demands of increasing rainfall intensity and highlight how sustainable strategies can effectively address extreme weather challenges while contributing to the restoration of natural environments within the city. In the case of using ‘gray’ solutions, only 10–20% of the area affected by floods is reduced. In comparison, a combination of gray and green infrastructure achieved an average reduction in peak water levels of 0.76 m.